Operation fortune : ruse de guerre [videorecording (DVD)] - Ritchie, Guy; Atkinson, Ivan; Davies, Marn; Statham, Jason, 1967-; Plaza, Aubrey, 1984-; Hartnett, Josh, 1978-; Elwes, Cary, 1962-; Malone, Bugzy, 1990-; Ferdinando, Peter; Marsan, Eddie; Grant, Hugh (Lionsgate, 2023)
Super spy Orson Fortune must track down and stop the sale of a deadly new weapons technology wielded by billionaire arms broker Greg Simmonds. Reluctantly teamed with some of the world's best operatives, Fortune and his crew recruit Hollywood's biggest movie star Danny Francesco to help them on their globe-trotting undercover mission to save the world.